If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(u + 6) = -2(5u + -7) + 6u Reorder the terms: 4(6 + u) = -2(5u + -7) + 6u (6 * 4 + u * 4) = -2(5u + -7) + 6u (24 + 4u) = -2(5u + -7) + 6u Reorder the terms: 24 + 4u = -2(-7 + 5u) + 6u 24 + 4u = (-7 * -2 + 5u * -2) + 6u 24 + 4u = (14 + -10u) + 6u Combine like terms: -10u + 6u = -4u 24 + 4u = 14 + -4u Solving 24 + 4u = 14 + -4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '4u' to each side of the equation. 24 + 4u + 4u = 14 + -4u + 4u Combine like terms: 4u + 4u = 8u 24 + 8u = 14 + -4u + 4u Combine like terms: -4u + 4u = 0 24 + 8u = 14 + 0 24 + 8u = 14 Add '-24' to each side of the equation. 24 + -24 + 8u = 14 + -24 Combine like terms: 24 + -24 = 0 0 + 8u = 14 + -24 8u = 14 + -24 Combine like terms: 14 + -24 = -10 8u = -10 Divide each side by '8'. u = -1.25 Simplifying u = -1.25
| 3(5x+2)=x+3 | | 70.00+x=74.30 | | 3x+7=10y | | x^3-3x^2-16x-12=0 | | 3[3-(-6x-7)]=90x+114 | | x+83= | | 2(x-4.40)=6.60 | | 3(t+1)=5(2t-5) | | 3x^2+3y^2-15x-30y=0 | | (2x^2-7)(8x^2+3)= | | 4y-16+8y=-4y | | 7(5x+2)=x+3 | | 4w+8= | | 4mn+3m+8n+6= | | 5w+5= | | 8x+9-4(x+1)=9x+7 | | 3p+80=-2p | | 3640=P(l+0.06*5) | | 8Y+9X=73.50 | | (3x+8)(6+x)=0 | | 4(3t+1)-7=t-(t+2) | | m-17/5-7m-7/4=3 | | 6-6(3x-4)=12 | | 3p-15=6p | | 2.4x+34.4=2.9-8.1x | | 25x^2-85x+81=0 | | x+x*0.07=100 | | x-401.94=144.23 | | 3y+9=2y-7 | | k=5x^6 | | 6x+7=4x+31 | | 4p+14=-14 |